87 DENDRITIC CELL-DEPENDENT INDUCTION OF BETA CELL-SPECIFIC REGULATORY T CELLS FOR SUPPRESSION OF AUTOIMMUNE DIABETES. (1st March 2007) - Pothoven, K.; Tarbell, K.; Yang, H.; Steinman, R. M.; Suthanthiran, M.; Luo, X.
Abstract : Background: Thymic-derived CD25 + CD4 + regulatory T (Treg) cells have been found to play an important role in the pathogenesis of autoimmune diabetes. Challenges for their application as a potent immunomodulatory therapy are (1) the small size of the naturally occurring CD25 + CD4 + Treg population and (2) the polyclonal nature of the existing CD25 + CD4 + Treg cells. Here we describe a novel system of using dendritic cell (DC)-stimulated expansion in the presence of TGF-β1 for in vitro generation of beta cell-specific CD25 + CD4 + T cells that are potent suppressors of autoimmune diabetes. Material and Methods: Naive BDC2.5/NOD CD25 − CD4 + cells were obtained by cell sorting from pooled BDC2.5/NOD LNs. Splenic DCs from NOD mice were purified by CD11c-positive selection. Naive CD25 − CD4 + T cells were either cultured with irradiated CD11c + DCs and BDC peptide (specific stimulation) or with anti-CD3 and anti-CD28 (nonspecific stimulation) for 7 days with or without TGF-β1, after which the CD25 + T-cell fraction was purified and analyzed. Results: Purity of the BDC2.5/NOD CD4 + CD25 − was routinely > 97%. At baseline, the CD4 + CD25 − BDC T cells express minimal Foxp3 measured by FACS analysis and real-time PCR. Stimulation in the presence of TGF-β1 with either specific or nonspecific conditions leads to marked induction of Foxp3 expression to a level comparable to that seen in naturally occurring CD25 + CD4 + Treg cells. This induction was not seen in the absence of TGF-β1. The induced CD25 + CD4 + Foxp3 + BDC T cells generated with DCs plus BDC peptide (specific stimulation) maintained a high level of cell surface clonotype expression after stimulation and exert antigen-specific suppression in in vitro suppression assays. When cotransplanted with syngeneic islets in diabetic NOD mice, these cells significantly prolonged islet graft survival from a median of 12 to 46 days ( p = .0008). When cotransferred with diabetogenic cells into NOD.scid recipients, theses cells significantly delayed the kinetics of diabetes onset ( p < .0001). In contrast, CD25 + CD4 + Foxp3 + BDC T cells induced with anti-CD3 and anti-CD28 (nonspecific stimulation) show lower levels of clonotype expression on cell surface and were unable to suppress BDC peptide-stimulated proliferation in vitro or protect islet grafts in vivo. Conclusion: Beta cell-specific BDC2.5 CD25 + CD4 + cells with high levels of Foxp3 can be induced from naive BDC2.5 CD4 + CD25 − cells by TGF-β1 in CD11c + DC-stimulated expansions. These cells harbor potent suppressive activity in an islet antigen-specific manner and suppress autoimmune diabetes.